Cross‐Conjugated Polycatechol Organic Cathode for Aqueous Zinc‐Ion Storage. Issue 1 (5th December 2019) - Zhang, Shuoqing; Zhao, Wentao; Li, Huan; Xu, Qiang
Abstract: The rapid development of aqueous zinc‐ion batteries poses a challenge for the exploration of cathode materials with high capacity and long cycle life. Organic materials are considered an appropriate choice owing to their structural flexibility and tunable surface chemistry. However, most organic cathode materials still have some shortcomings, such as low electrical conductivity, high cost, and limited cycling durability. Here, a facile synthesis of a novel organic composite cathode composed of cross‐conjugated polycatechol (PC) combined with graphene (PC/G) is reported. The PC/G cathode is used for aqueous zinc‐ion storage, wherein many hydroxy groups in the PC/G composite cathode can be converted into redox‐active carbonyl groups at the initial discharge–charge. This composite cathode can deliver a high specific capacity of 355 mAh g −1 at 0.1 C and a specific capacity of 171 mAh g −1 at 10 C. Moreover, the composite cathode can retain 74.4 % of its initial capacity after 3000 discharge–charge cycles at 2 C. This coordination route to zinc ions within the PC/G composite cathode can avoid the destruction of the cathode material during discharge–charge. This organic cathode shows great promise for reversible zinc‐ion storage, bringing aqueous zinc‐ion batteries a step closer to future practical applications. Abstract : Zinc‐ion batteries : A novel organic composite cathode of cross‐conjugated polycatechol (PC) combined with graphene (PC/G) is reported, in which many of the hydroxy groups in the PC/G composite cathode can be converted into redox‐active carbonyl groups at the initial discharge–charge. This organic cathode shows excellent electrochemical performance for reversible zinc‐ion storage.